Morphological and molecular evidence reveal a new species of the earthworm genus Pontodrilus Perrier, 1874 (Clitellata, Megascolecidae) from Thailand and Peninsular Malaysia - Seesamut, Teerapong; Sutcharit, Chirasak; Jirapatrasilp, Parin; Chanabun, Ratmanee; Panha, Somsak (Zootaxa, 2018)
A new species of the megascolecid earthworm genus Pontodrilus Perrier, 1874, Pontodrilus longissimus sp. n., is described from seashores of Thailand and Peninsular Malaysia. The new species differs from congeners, especially the cosmopolitan P. litoralis (Grube, 1855) in the size of the body, number of segments and the shape of the spermathecae. P. litoralis is redescribed, based on specimens collected from the same region and the same type of habitat. DNA fragments of the mitochondrial cytochrome oxidase subunit I of both species were sequenced. Morphological as well as DNA sequence-based comparisons confirm that P. longissimus sp. n. is a lineage distinct from P. litoralis and in fact a new species. The illustrated descriptions are accompanied by a key to species of Pontodrilus.